Impulsively Reflected Ions: A Plausible Mechanism for Ion Acoustic Wave Growth in Collisionless Shocks. Issue 3 (28th March 2019) - Goodrich, Katherine A.; Ergun, Robert; Schwartz, Steven J.; Wilson, Lynn B.; Johlander, Andreas; Newman, David; Wilder, Frederick D.; Holmes, Justin; Burch, James; Torbert, Roy; Khotyaintsev, Yuri; Lindqvist, Per‐Arne; et al.
Abstract: We present recent high time resolution observations from an oblique (43°) shock crossing from the Magnetospheric Multiscale mission. Short‐duration bursts between 10 and 100 ms of ion acoustic waves are observed in this event alongside a persistent reflected ion population. High time resolution (150 ms) particle measurements show strongly varying ion distributions between successive measurements, implying that they are bursty and impulsive by nature. Such signatures are consistent with ion bursts that are impulsively reflected at various points within the shock. We find that, after instability analysis using a Fried‐Conte dispersion solver, the insertion of dispersive ion bursts into an already stable ion distribution can lead to wave growth in the ion acoustic mode for short durations of time. We find that impulsively reflected ions are a plausible mechanism for ion acoustic wave growth in the terrestrial bow shock and, furthermore, suggest that wave growth can lead to a small but measurable momentum exchange between the solar wind ions and the reflected population. Key Points: Ion acoustic waves are observed in an oblique terrestrial bow shock crossing Ion acoustic waves are observed alongside evidence of dispersive ion beams along with solar wind and reflected ion populations Instability analysis shows that dispersive ion beams can allow ion acoustic wave generation in an already stable ion distribution